PENGARUH PELAKSANAAN KELOMPOK KERJA GURU TERHADAP KEDISIPLINAN DAN KEMAMPUAN PROFESIONAL GURU SEKOLAH DASAR NEGERI 14 BANGLAS - Risdianto Risdianto; Ramdhan Witarsa; Masrul Masrul (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
The implementation of elementary school teachers' working groups is very important to be carried out regularly in order to build understanding among teachers on the quality of learning. This research aims to measure how much influence the implementation of teachers' working groups has on the discipline and professional skills of elementary school teachers. The method used in this research is the quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting the research problem, developing research hypotheses, creating a research design, conducting pretests, conducting experiments, conducting post-tests, processing and analyzing data, and drawing conclusions. The research sample amounted to 18 teachers, consisting of 9 teachers in the experimental class and 9 teachers in the control class. The data collection technique used was observation of teacher discipline and professional skills. The results showed that the implementation of teachers' working groups had a significant effect on the discipline and professional skills of elementary school teachers in the experimental class. The implementation of the teachers' working group should be carried out continuously and its quality should be improved so that it can have more influence on other aspects of teacher performance.